SIMILARITIES AND DIFFERENCES OF CASE IN ENGLISH AND UZBEK LANGUAGE GRAMMAR - ASATOVA AZIZA (TADQIQOTLAR.UZ, 2024)
ABSTRACT This paper examines the case systems of English and the Uzbek language, analyzing both the similarities and key differences between the two. English is known for its relatively simple case system, with only a distinct possessive case ('s) and a few remnants of the historical case system. In contrast, Uzbek is a Turkic language with a more complex case structure, featuring several distinct cases that convey different grammatical and semantic functions.The analysis will cover the core cases present in each language, including the nominative, accusative, dative, and genitive cases. It will explore how these cases are formed and used in sentence structures, as well as any nuances or additional cases that exist. Key similarities that will be discussed include the general concept of grammatical case to indicate the role of nouns and noun phrases in a sentence. However, the paper will primarily focus on the substantial differences, including the more robust case system in Uzbek compared to the largely vestigial case system in English.The goal is to provide a comprehensive comparison that highlights the unique characteristics of each language's case grammar, offering insights into the typological differences between these Indo-European and Turkic language families. This analysis will be valuable for linguists, language learners, and anyone interested in cross-linguistic explorations of morphological structures..